School Stress Coping Styles and Self-Esteem Interconnections in Adolescence - Pileckaitė-Markovienė, Margarita; Stanišauskaitė, Aušra (Acta Paedagogica Vilnensia, 2005)
The aim of this investigation is to analyse the interconnections of coping of school stress styles and self-esteem. Comparison of coping styles of adolescents with high, average and low self-esteem is made in the article. Results show that adolescents with higher self-esteem more often use problem solving way and adaptive avoidance way of coping with school stress in comparison with adolescents with lower self-esteem.
Keywords: adolescents; school stress; coping; self-esteem